Iron Man [videorecording (Blu-Ray)] - Downey, Robert, Jr., 1965-; Howard, Terrence; Bridges, Jeff, 1949- (Marvel Studios, 2017)
A wealthy industrialist is held captive in enemy territory and escapes by building a high-tech suit. When he returns home, he decides to use his money, talents, and suit to save the world. Includes additional scenes, featurettes, and more.